استراتيجيتي تسلق التلة والتعلم معا واثرهما في تحصيل مادة قواعد اللغة العربية عند طلاب المرحلة الاعدادية - زامل كاظم الموسوي حيدر (Journal of College of Education, 2021)
The current research aims to know The impact of strategic Hill Climping and learnin Together in the acquisition of Arabic grammar the preparatory stage by the student Directorate General for Education Baghdad Rusafa Third,’s (13), the researcher chose Qsidia school (kotaba high of Benin) to apply the experience. Having identified the researcher the school that will be applied when the experiment has had, whispers to her of three divisions for the for literature are (a, b,c) were selected randomly Division (a) to represent the experimental group won, and Division (b) to represent the experimental group tow , Division (c) to represent the control group, the total number of students in three divisions (96) students , (32) students in the groups three . Promising researcher achievemen test in, the acquisition of Arabic grammar By fourth stage - scientific branch student in the subjects to be studied during the period of the experiment (7) items in light of the content of the textbook for the fourth stage - scientific branch, and behavioral objectives prepared by the strategic Hill Climping and learnin Together in the acquisition of student research sample. researcher studied the groups three during the period of the experiment and continued (11) week , and used the following statistical methods: ANOVA and sheffe formula, and Chi-square, and Kuder Richardson-20 in analyzing the results of his research. Have shown the search 1. result than students of the first experimental group to the students of the control group . 2. result than students of the second experimental group to the students of the control group . 3. result than students of the first experimental group to the students of the second experimental group . and shows the result the following , that HILL CLIMP AND LEARNIN TOGETHER , STRATEGy , have positive impact in increasing the acquisition by scientific fourth students , which shows its importance in raising the scientific level